An enhanced electrochemical properties of novel tin based layered Li(Ni–Sn–Mn)O2 cathode material for rechargeable Li-ion batteries. (24th May 2019) - Kumar, Gopika G; Kumaraguru, S; Partheeban, T; Sasidharan, M; Kumaran, V; Rajkumar, P; Subadevi, R; Sivakumar, M; Gnanamuthu, RM
Abstract: In this work, the synthesis of newly prepared cathode material, Li(Nix Sny Mnz )O2, which is used as a positive electrode material and is suitable for energy storage and conversion in lithium-ion rechargeable batteries, are taken into account. Indeed the main goal is to replace the conventional cathodes such as lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate in view of achieving higher capacity, long cycle life, and better environmental compatible compounds. The stoichiometric ratio of the Li(Ni0.4 Sn0.3 Mn0.3 )O2 material exhibits better performance, after evaluating with various other ratios and it is prepared via a hydrothermal process using Teflon lined autoclave reactor vessel and followed by calcination technique. Furthermore, the prepared material is subjected to XRD, FE-SEM with EDAX, TEM analysis, and also the electrochemical test has been assessed. It includes electrochemical impedance spectroscopy and electrochemical charge-discharge studies using Li/Li(Ni0.4 Sn0.3 Mn0.3 )O2 coin type half-cell (2032 size) at the 0.1 C rate and the voltage range between 4.3–2.5 V. From the electrochemical studies, it has been found that the first charge-discharge capacity obtained of 192 mAh g −1 and 176 mAh g −1, respectively. Thus, the battery efficiency acquired is 97% and it has been maintained after the 1st cycle with a good cyclability also without huge fading. It may be a suitable positive electrode in the half cell Li-ion rechargeable batteries.